2015
DOI: 10.1134/s1063074015030098
|View full text |Cite
|
Sign up to set email alerts
|

Fucoidans of brown algae: Biosynthesis, localization, and physiological role in thallus

Abstract: The issues of the structure and biosynthesis of fucose containing sulfated polysaccharides are considered in this review; the data on the localization of fucoidans in tissues and their significance for algae are provided. Fucoidans participate in the building of cell walls and the support of their structure, as well as in extrusion of spores and gametes from reproductive organs. Due to the sulfated groups, these polysaccha rides can bind cations (mainly K + , Na + , Ca 2+ , Mg 2+ ) and participate in ion excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 105 publications
(120 reference statements)
0
27
0
1
Order By: Relevance
“…Fucans are high-molecular-weight sulfated polysaccharides, present in the intercellular tissues or mucilaginous matrix of brown algae [75]. Beside many bioactivities, such as antiproliferative, antiadhesive properties can protect the cells from viral infections [76].…”
Section: Marine Antioxidants and Antiviral Activitymentioning
confidence: 99%
“…Fucans are high-molecular-weight sulfated polysaccharides, present in the intercellular tissues or mucilaginous matrix of brown algae [75]. Beside many bioactivities, such as antiproliferative, antiadhesive properties can protect the cells from viral infections [76].…”
Section: Marine Antioxidants and Antiviral Activitymentioning
confidence: 99%
“…Thus, screening for natural products capable of inducing apoptosis in cancer cells that can be used collaterally with other cytotoxic drugs is of interest in order to elevate the therapeutic efficacy and reduce the side effects in cancer therapy. In this study, fucoidan (FUC), a natural polysaccharide composed of sulphated L-fucose residues extracted from marine brown algae http://etd.uwc.ac.za/ (Phaeophycophyta) and some echinoderms (sea urchin and sea cucumber) [7,10,13,17,20,21,61,62] was tested for its potential anticancer effects alone or in combination with cisplatin, doxorubicin and taxol against non-malignant MCF-12A breast epithelial cells and MCF-7 cancer cells.…”
Section: Problem Statementmentioning
confidence: 99%
“…A and B: One Way ANOVA, using Tukey's multiple comparisons test, indicated that the differences in the mean values among the treatment groups are greater than would be expected by chance, i.e., there is a statistically significant difference (p<0.001), except for treatments indicated in the text. [7,8,10,17,20,21,61,62,426,459,471,472,482,483,494,510,515,[517][518][519][520][521].…”
Section: And Mcf-12a Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fucoidan, a marine sulfated polysaccharide, is mainly found in extracts from brown algae and brown seaweed [133]. Many researchers have studied the therapeutic effects of fucoidan on osteoarthritis [134], cancer [135], diabetes [124], obesity [136], and kidney [137] and liver disease [138].…”
Section: Promising Epc-based Therapeutic Strategies Against Cvdsmentioning
confidence: 99%